Public international law: a practical approach, 3rd ed. - Hamid, Abdul Ghafur@Khin Maung Sein (Sweet & Maxwell Asia, 2011)

(untitled)
This new edition has been completely revised and extensively rewritten to cover the rapid development in this branch of law brought about by a number of landmark rulings decided by the International Court of Justice and other international courts and tribunals. Amongst the rapidly developing areas are the law of State responsibility, international human rights law, and the law on the use of force – these are fully reflected in the updated contents of this book.